2019
DOI: 10.1021/acs.jpcc.9b03104
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Fluorescence Spectroscopy of Quantum Emitters Coupled with Plasmonic Dimers and Trimers

Abstract: We have developed a theory for the photoluminescence of dimer nanohybrids and trimer nanohybrids using the density matrix method. These nanohybrids are made from identical double metallic nanoshells embedded in an ensemble of quantum emitters. We consider that they are immersed in medical, biological, and chemical solutions. The dipole−dipole interaction between quantum emitters in the ensemble is calculated using the mean-field approximation. The effect of the dipole−dipole interaction has been included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Although many studies have shown that such an approach is valid, one should be aware of possible quantum effects in NP coupling when particle sizes are small (less than 10 nm) or the gap distance between the NPs is in the subnanometer range . Additionally, interactions of molecular dyes or quantum dots with plasmonic NPs are fundamentally dictated by quantum electrodynamics, although the mean-field approach has been applied to describe the dipole–dipole interaction in these hybrid systems. , The near-field spectra obtained in the current study might provide additional insights to these hybrid systems.…”
Section: Discussionmentioning
confidence: 90%
“…Although many studies have shown that such an approach is valid, one should be aware of possible quantum effects in NP coupling when particle sizes are small (less than 10 nm) or the gap distance between the NPs is in the subnanometer range . Additionally, interactions of molecular dyes or quantum dots with plasmonic NPs are fundamentally dictated by quantum electrodynamics, although the mean-field approach has been applied to describe the dipole–dipole interaction in these hybrid systems. , The near-field spectra obtained in the current study might provide additional insights to these hybrid systems.…”
Section: Discussionmentioning
confidence: 90%
“…Note that the distances between individual QDs in the system are chosen to be the same order of magnitude or larger than the characteristic SPP wavelength in the system. Considerable reduction of such a distance can lead to an increase in the role of near-field dipole-dipole interaction (DDI) between nanoparticles (NPs) [42][43][44] and changing the regime from plasmonic waveguide to non-radiative energy transmission by means of photonic bound states. [45] In our investigation, we use a semiclassical approach to define the graphene waveguide system's main parameters with an Ag 2 Se QD array that can lead to the excitation of graphene SPPs only in the local space between the gold stripes used to connect external electrical voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Due to recent advancements in nanofabrication techniques, there has been growing interest in SQD–MNP hybrid nanostructures for their potential novel optoelectronic applications , and exotic physical behavior, including plasmon–exciton electromagnetic coupling, plasmon-assisted Rabi oscillations, as well as plasmon-modified energy transfer and resonances. ,,, A wide range of theoretical studies on nanostructures have been developed, based on classical, semiclassical, ,, and full quantum mechanical approaches. , These studies have greatly motivated extensive exploration toward nonlinear optical fields, such as second harmonic generation, , optical bistability, , four-wave mixing, Raman scattering, giant third-order nonlinear responses, and high-order harmonics . Recently, Singh et al developed density matrix method for nanohybrids and observed the anomalous quenching and enhancement in the photoluminescence (PL) spectrum of the CdSe/ZnS quantum dot embedded in the ensemble of Au MNP .…”
mentioning
confidence: 99%
“…Recently, Singh et al developed density matrix method for nanohybrids and observed the anomalous quenching and enhancement in the photoluminescence (PL) spectrum of the CdSe/ZnS quantum dot embedded in the ensemble of Au MNP . They demonstrated fluorescence enhancement in dimer and trimer nanohybrids …”
mentioning
confidence: 99%
See 1 more Smart Citation